Patient preferences concerning the efficacy and side-effect profile of schizophrenia medications: a survey of patients living with schizophrenia - Eric Achtyes; Adam Simmons; Anna Skabeev; Nikki Levy; Ying Jiang; Patricia Marcy; Peter J. Weiden (BMC Psychiatry, 2018)
Abstract Background Despite the availability of numerous antipsychotic medications, many patients with schizophrenia continue to experience side effects that contribute to the overall burden of the illness. The present survey of patients with schizophrenia and schizoaffective disorder aimed to assess patient attitudes toward antipsychotic treatment, and understand key factors about willingness to try a new medication. Methods A cross-sectional survey was administered to 250 patients with a primary clinical diagnosis of a schizophrenia spectrum disorder across five outpatient clinics in the United States. The survey included self-reported gender, age, weight, and height, and questions about the importance of efficacy and side effects on the decision to take a prescribed antipsychotic medication. Results Patients rated efficacy and side effects as important attributes of antipsychotic treatment, with 93.6% and 83.6% of patients listing these as “very” or the “most” important factors in taking prescribed medication. A total of 87.6% of respondents identified the ability to think more clearly as an important property of their medication. Patients identified weight gain, physical restlessness, and somnolence as important side effects of current treatments (“very” or “most” important by 61.6%, 60.8%, and 58.8%, respectively). When asked about willingness to change antipsychotic medication, anticipated weight gain had a negative influence on willingness to try the new treatment, with 22.0% declining to try a medication that would lead to weight gain of 2.7–4.5 kg (6–10 lb), 34.0% declining for anticipated weight gain of 5.0–9.1 kg (11–20 lb), and 52.4% declining for anticipated weight gain greater than 9 kg (20 lbs). Conclusion Patients living with schizophrenia spectrum disorders are influenced by many factors when considering whether to take their medication, including efficacy and side effects. It is important for clinicians to assess specific patient concerns to develop a comprehensive treatment plan that maximizes adherence to the prescribed therapy.